PENGUJIAN ANTESEDENT DARI NIAT PENGGUNA INTERNET DALAM KEPUTUSAN BERTRANSAKSI MENGGUNAKAN E-COMMERCE - Trie Sartika Pratiwi (Universitas Indo Global Mandiri)
This study aims to find empirical evidence about the antecedents of the intention of testing Internet users consisting of several factors in the decision to trade through e-commerce. The subjects were 175 consumers of Internet users in Indonesia through a mailing list. This study uses a questionnaire survey instrument. This study identifies the extent to which the reference (antesedent) of intention (intention) of internet users against decisions transactions through e-commerce. In this study tested the hypothesis that there are 10 and 9 hypothesis is proven using software SMARTPLS. From the results of this study indicate that the intention of Internet users in the decision transactions through e-commerce is affected by the privacy, security, confidence (trust), the perception of risk (perceived risk), perceived ease of use (perceived ease of use), the benefits perceived (perceived usefulness ). Keywords: Antecedent, Trust, Perceived Risk, Perceived Ease of Use, Perceived Usefulness, Intention, e-Commerce